FACTORS INFLUENCING WORK FATIGUE IN TRAIN DISPATCHER AT BANDUNG STATION - Handoko Handoko; Atik S. Kuswati; Safrudin Kurniawan; Panji Bintang Samodra; Kartini Harahap (Jurnal Ekonomi, 2023)
Train dispatcher who is absent it causes an overhaul of the service pattern; there are nine to eleven times the SPV Perka replaces Train Dispatcher in one month. This high intensity of replacement was caused by the absence of the relevant train dispatcher, as a result of the fatigue factor experienced by the officers. It can be interpreted that it is important to minimize the level of work fatigue in Train Dispatcher by paying attention to the factors that affect work fatigue, both internal and external factors. Based on these problems, the researchers seek to analyze the factors that influence work fatigue in Train Dispatcherat Bandung Station. This research uses quantitative methods with primary and secondary data sources. The data collected through a questionnaire to all relevant train dispatcher, on the Bandung station, for January-March 2022. Data processing techniques were carried out on Microsoft Excel and SPSS version 25 applications with multiple linear regression analysis and to measure the level of officer fatigue, the Subjective Self Rating Test method was used. The results of this research were 18 officers get low fatigue and 6 people moderate fatigue. Factors that affect work fatigue are age and nutritional status, with a percentage of 52.9% while the rest is influenced by other factors.